EVALUATION OF SUBGRADE CAPACITY OF JIMMA SOILS USING DCP TEST: A CORRELATION OF CBR AND DCPI (Malaysian Journal of Civil Engineering, 2018)
Subgrade strength of soils is usually evaluated using California Bearing Ratio (CBR) values. As the cost and time required to conduct CBR test are high, dynamic cone penetrometer (DCP) would be recommended and CBR value can be estimated later from DCP result using a correlation formula. In this paper, laboratory CBR of Jimma fine-grained soils has been correlated with field DCP values referring to the physical properties such as natural moisture content and field density; as these factors significantly influence the behaviour of subgrade soils. Different techniques were used to demonstrate relations that best suit to find values of CBR from DCP test. Equations were developed between CBR and dynamic cone penetrometer index (DCPI) for the total of 36 sample points and adjusted coefficient of determination becomes 0.84. A validation was also done to test the applicability of the developed correlation formula for the local soils with the given physical conditions. The correlation gave a promising relationship between CBR and DCP and can be applicable for preliminary design purpose with the due consideration of the locality circumstances.